Geoinżynierska ocena ochrony przeciwpowodziowej szpitala w Słubicach - Kołodziejczyk, Urszula (Wydawnictwa AGH, 2011)
The extreme river water stages cause intensive seepage on flooded area, normally protected by levees. The example of this is town Slubice (Lubuski District), situated in 2 m lower than alarm water level. The paper describes the geoengineering opinion relating the quality of embankments in Slubice focused on the intensivity of water percolation from Odra bed to the terrains outside levees, where the hospital is situated. The modernization in 1999 limited, but not eliminated, the water percolation through the banks and, due to financial deficiency, did not included the proper condensation of subsoil and the body of banks, where, as it was proved by geotechnical analysis, still remain parts of soil of loose or average structure and parts of soil rich in organic matter. New flood protection solutions in Slubice are necessary and as long as they are not become realized, the town would fight against the excess of water percolating from Odra river bed.

Ekstremalne stany wody w rzekach powodują intensywne przesiąki na tereny zalewowe, zwykle chronione wałami przeciwpowodziowymi. Przykładem jest miasto Słubice (województwo lubuskie), położone w dwumetrowej depresji w stosunku do alarmowego wezbrania wód w Odrze. Artykuł dotyczy geoinżynierskiej oceny stanu wałów przeciwpowodziowych w mieście Słubice, a głównie - intensywności filtracji wody z koryta Odry na teren zawala, gdzie zlokalizowany jest szpital. Modernizacja wałów przeprowadzona tutaj w 1999 r. zredukowała, ale - nie wyeliminowała filtracji wody przez wał; ze względu na niedobór środków nie objęła właściwego dogęszczenia podłoża i korpusu wałów, gdzie - jak wykazały aktualne badania geotechniczne - ciągle znajdują się fragmenty gruntów średnio zagęszczonych i luźnych, a także pakiety gruntów bogatych w substancję organiczną. Nowe rozwiązania przeciwpowodziowe w Słubicach są nieodzowne i dopóki nie zostaną zrealizowane, miasto będzie nieustannie walczyło z nadmiarem wody przesączającej się z koryta Odry.
Geoengineering opinion relating flood protection of the hospital in Slubice (Poland)
Górnictwo i Geoinżynieria
Bibliogr. s. 366.
Keywords: flood; powódź; embankments; wał przeciwpowodziowy; percolation; filtracja